A colorimetric sensor for hydrogen sulfide detection using direct inhibition of active site in G-quadruplex DNAzyme. (April 2017) - Kang, Seungyoon; Oh, Jinyoung; Han, Min Su
Abstract: Because of the toxicity of hydrogen sulfide and its important role in various physiological processes, the development of a selective and sensitive hydrogen sulfide sensing method is vital. In this study, a colorimetric method for hydrogen sulfide detection was developed by exploiting the direct inhibition of active site in G-quadruplex DNAzyme by hydrogen sulfide. Hydrogen sulfide inactivates the peroxidase-like activity of PS2.M-hemin G-quadruplex DNAzyme by directly blocking the active site of the DNAzyme, allowing the label-free colorimetric detection of hydrogen sulfide by the naked eye by using 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS 2− ) as a peroxidase substrate. From titration results, the detection limit of this colorimetric hydrogen sulfide sensor was estimated to be 410 nM. In addition, the sensor is highly selective for hydrogen sulfide over various anions and was used to determine hydrogen sulfide concentrations in tap water samples. Graphical abstract: Highlights: A colorimetric sensor for hydrogen sulfide was developed using G-quadruplex DNAzyme. This sensor utilize direct inhibition of active site in G-quadruplex DNAzyme by hydrogen sulfide. This sensor was selective for hydrogen sulfide in the presence of other anions. The detection limit of this colorimetric sensor system is estimated to be 410 nM.